Some new rotatable designs based on the buckminsterfullerene molecule - Bacon, D. Eric; Herzberg, Agnes M. (Utilitas Mathematica, 2000)
Different response surface designs may possess different properties. The abundance of recent research on the buckminsterfullerene molecule stimulated this investigation of the properties of the buckminsterfullerene structure as an experimental design. The precision of the estimates of the parameters in the models from these designs and their robustness against missing observations are investigated and compared with those of other well-known designs, in particular rotatable designs.